1987
DOI: 10.1017/s0014479700017142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gypsum and Drought on Pod Initiation and Crop Yield in Early Maturing Groundnut (Arachis hypogaea) Genotypes

Abstract: SUMMARYGypsum application and irrigation increased yield in early maturing groundnut genotypes in experiments using line source and conventional irrigation. Response to gypsum varied with genotype; with some gypsum increased yields at all water application rates, in some genotypes there was no response, while with others gypsum increased yield in drought conditions.In a separate study of the effect of gypsum and drought on pod initiation and development in three groundnut genotypes, gypsum did not greatly infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…Although adequate calcium (as gypsum) was applied to the podding zone of all plants in this study, there are numerous reports that drought can decrease calcium uptake and thus induce calcium deficiency in peanuts (Gillier 1969;Hallock and Allison 1980;Rajendrudu and Williams 1987). Calcium is absorbed from the soil mainly by the subterranean pegs and developing pods, while calcium uptake by roots is not usually available for pod growth and development (Beringer and Taha, 1976;Wiersum 1951).…”
Section: Discussionmentioning
confidence: 97%
“…Although adequate calcium (as gypsum) was applied to the podding zone of all plants in this study, there are numerous reports that drought can decrease calcium uptake and thus induce calcium deficiency in peanuts (Gillier 1969;Hallock and Allison 1980;Rajendrudu and Williams 1987). Calcium is absorbed from the soil mainly by the subterranean pegs and developing pods, while calcium uptake by roots is not usually available for pod growth and development (Beringer and Taha, 1976;Wiersum 1951).…”
Section: Discussionmentioning
confidence: 97%
“…Similar experiments elsewhere have found that soil water deficits during pegging and pod development decrease yield primarily by reducing pod numbers (Pallas etal. 1979;Rajendrudu and Williams 1987). Calcium deficiency caused by low soil water content in the podding zone has also been shown to strongly influence pod initiation and development under drought conditions (Gillier 1969;Skelton and Shear 1971;Hallock and Allison 1980), and may have contributed to the poor reproductive development in this experiment.…”
Section: Discussionmentioning
confidence: 73%
“…However gypsum (500 kg ha-1) was applied to all plots at 20 DAP, a practice which has been shown to increase the percentage of developed pods (Radder and Biradar 1973). Rajendrudu and Williams (1987) have recently demonstrated that the response to gypsum can vary with genotype and pattern of drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…Neverthe less, the percentage of pegs that progressed to form pods (> R4 stage) by 47 to 49 d after tagging was reduced from a combined average of 81% in irrigated treatments to 57% in stressed treatments (Table 4). Rajendrudu and Williams (1987) also reported that drought reduced the percentage of pegs that developed into pods. Drought stress reduced the pod growth rates of both the pods tagged before and after the rain-exclusion treat ment was initiated ( Fig.…”
Section: Resultsmentioning
confidence: 95%